Diagnosis of malignant bone tumors in children - Małek, Anna; Wysokińska, Olga; Iwaniszyn-Zapołoch, Klara; Zadrożna, Karolina; Sidorczuk, Piotr; Fabiś, Mateusz; Wójcik, Bartłomiej; Żyga, Justyna; Klajda, Katarzyna (Journal of Education, Health and Sport, 2022)
Bone cancers occur mainly in adolescents and young adults, and benign lesions are more frequent than malignant ones. The most common malignant tumors include osteosarcoma, Ewing’s sarcoma and chondrosarcoma. The course of the disease may not be obvious and symptoms may be ambiguous, so it is important to catch them early and take appropriate action. Laboratory tests such as CRP, ESR, LDH, ALP may prove useful in the diagnosis of bone neoplasms in children. All children with suspected malignant bone cancer should undergo an x-ray examination. MRI, CT scans are performed to expand the diagnosis and determine the extent of the disease. The basis of diagnosis is histopathological examination. The result of this study is very important in the selection of therapeutic procedures, it influences decisions regarding the scope and degree of radicality of the operation. It is crucial that the entire diagnostic process is carried out in highly specialized centers that have extensive experience in the diagnosis and treatment of malignant bone tumors in children. It is most beneficial to conduct diagnosis and treatment at the same center, and preferably by the same team of specialists. This team should include doctors from orthopedics, radiology, oncology, radiation therapy and pathomorphology. Conducting diagnosis and treatment in highly specialized centers has a positive effect on the prognosis and quality of life of patients. The purpose of this article is to highlight the early and uncharacteristic symptoms of bone cancer in children and to present the complexity of the diagnostic process, as well as the importance of carrying it out in highly specialized centers with extensive experience in treating pediatric bone malignancies.